As demonstrações contábeis como instrumentos auxiliares nas tomadas de decisões no IFAM/Campus Tabatinga - Silva, Kleyton Sérgio da (Brasil, 2022)
The purpose of this paper is to identify which statements were used and in which situation. The purpose of this article is to identify which statements were used and in which situation were consulted. The applied methodology was documentary consultations and a direct questionnaire with all statements required by law in a short answer: yes or no, and giving the explanation of reporting the facts or acts that the tools were consulted, and, positive results were obtained regarding the use of the statements. Public organizations make their management of resources as well as private entities, but their mission is to assist society with public goods and services, resulting from the application of resources in those units. In this essentially public organization, it is incumbent only on the expenditure author - the unit manager - to make decisions on the allocation of financial resources in order to prioritize the collective interest and zeal with the public patrimony